Facilitating prevention in primary care. Issue 6458 (8th December 1984) - Fullard, E; Fowler, G; Gray, M
Abstract : We believe that many general practitioners would practice preventive medicine if they had the opportunity to organise their practice to do this. We therefore provided a "facilitator, " who understands the work of a general practice, to help practices that were interested in prevention to set up programmes. She, for example, helped the primary care team to set up objectives, trained practice nurses to measure blood pressure, and set up a system to measure the progress of the programme.